PERAN KEPOLISIAN DAN KEJAKSAAN DALAM PENEGAKAN HUKUM DI INDONESIA - Nurafrizal, Alvin (Maliki Interdisciplinary Journal, 2025)
Law enforcement in Indonesia is inseparable from the strategic role of the police and the prosecutor's office, as two key institutions in the criminal justice system. The police are tasked with conducting inquiries, maintaining public order, and gathering evidence for court proceedings. The prosecutor's office acts as the public prosecutor, ensuring that the legal process follows the rules, including the execution of court decisions. Collaboration between these two institutions is crucial for creating an effective, fair, and transparent legal process. However, in practice, various challenges remain, such as weak coordination, differing legal interpretations, limited resources, and issues of officer integrity. Reform efforts through improving human resource competency, strengthening internal oversight, and utilizing digital technology are crucial solutions to improve the effectiveness and accountability of law enforcement. With strong synergy between the police and prosecutor's office, and active community participation, it is hoped that law enforcement in Indonesia will be more professional, transparent, and trusted by the public.